Effectiveness of ursodeoxycholic acid therapy in intrahepatic cholestatsis of pregnancy - Pitale, Devdatt I.; Jadhav, Sujata N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy specific disorder and commonly presents with maternal pruritus, abnormal liver function tests and adverse maternal -foetal outcomes. ICP lacks protocol-based therapy as etiology is multifactorial and is based on symptomatic treatment. The overall incidence of ICP is variable from 0.1 to 15.6% worldwide. The aim of this study is to assess the effectiveness of UDCA in ICP with regards to reduction in pruritus, normalizing LFTs and maternal-foetal outcomes. Methods: This multicentric prospective study was performed from June 2017 to December 2019 in pregnant women with ICP attending the Antenatal clinic at INHS Patanjali, MH Dehradun, INHS Asvini, INHS Sandhani. In this study, 50 women with ICP. who satisfied the inclusion and exclusion criteria were started on UDCA therapy. The effectiveness of therapy was evaluated on the basis of normalization of LFT levels, reduction in pruritus, safe confinement, maternal-foetal outcomes and adverse effects if any Results: The pregnant women with ICP on UDCA therapy showed marked improvement in pruritus, near normal LFT levels. After the UDCA therapy the frequency and intensity of pruritus was reduced in 50 (100%) of women. Safe confinement was achieved, with normal delivery in 45 (90%) women with no any major adverse effects and adverse maternal-foetal outcomes. Conclusions: This study shows the effectiveness of URCA therapy in reducing the ICP associated pruritus, normalizing LFTs and safe confinement without any major adverse effects. UDCA therapy is an effective and safe option in ICP.